Effect of storage length on early stand establishment of four sorghum (Sorghum bicolor L.) varieties in the smallholder sector of Zimbabwe - Madanzi, Tendai; Muhambi, M.; Manjeru, Pepukai; Makeredza, B.; Darikwa, T.B. (African Crop Science Society, 2016)
Sub-optimal crop establishment is one of the major constraints to sorghum production in the smallholder sector of Zimbabwe attributed to the use of farm-retained seed subjected to long and poor storage conditions. A study was carried out to determine optimum storage length that results in optimum stand establishment. Standard germination and vigor tests were carried out to determine loss of vigor due to storage length (one to three years after harvest) on four sorghum varieties (Marcia, SV2, SV3, and SV4). A field experiment was also carried out to determine the effects of seed storage length on emergence of sorghum. The experiment was laid out in a split-plot with four replications. Storage length was the main-plot factor with 3 levels and variety was the subplot factor. The interaction (P<0.001) between variety and storage length after the vigor test was significant. There was a general decrease in vigor with increased storage length with variety Macia maintaining a high germination after 3 years of storage. The other varieties had a germination less than 50 % after year one. In the field, there was significant difference (P<0.05) due to variety on emergence. Variety SV3 achieved the highest emergence of 56.8 % while Macia, SV4, and SV2 had 52.5 %, 39.3 %, and 34.2 % respectively. Conclusively, Macia and SV3 can be grown beyond year one and give reasonable stand establishment.